Simplify 2^3

9 answers

To simplify \( 2^3 \), you calculate \( 2 \times 2 \times 2 \).

So,

\[ 2^3 = 2 \times 2 \times 2 = 8 \]

Thus, \( 2^3 = 8 \).

Simplify using exponents 3×3×3×3

The expression \( 3 \times 3 \times 3 \times 3 \) can be simplified using exponents. Since there are four 3's being multiplied together, you can express this as:

\[ 3 \times 3 \times 3 \times 3 = 3^4 \]

So, the simplified form using exponents is \( 3^4 \).

Simplify −4^2

To simplify \(-4^2\), you need to be careful with the placement of the negative sign and the exponent.

According to the order of operations, the exponent is applied first. So, calculate \(4^2\) first:

\[ 4^2 = 16 \]

Then, apply the negative sign:

\[ -4^2 = -16 \]

Therefore, the simplified result is \(-16\).

If you meant \((-4)^2\), that would be a different calculation:

\[ (-4)^2 = (-4) \times (-4) = 16 \]

But as written, \(-4^2\) simplifies to \(-16\).

−5×−5×−5×−5 is equvalent to -5^4

The expression \(-5 \times -5 \times -5 \times -5\) can be simplified as follows:

When you multiply an even number of negative numbers, the result is positive. Here, we have four negative fives:

\[ (-5) \times (-5) \times (-5) \times (-5) = [(-5) \times (-5)] \times [(-5) \times (-5)] = 25 \times 25 = 625 \]

This can also be expressed using exponents. Since there are four instances of \(-5\), you can write it as:

\[ (-5)^4 \]

However, the expression \(-5^4\) is not equivalent to \(-5 \times -5 \times -5 \times -5\). Instead, \(-5^4\) is calculated as:

\[

  • (5^4) = - (625) = -625 \]

So, in summary:

  • \(-5 \times -5 \times -5 \times -5 = (-5)^4 = 625\)
  • \(-5^4 = -625\)

Thus, \(-5 \times -5 \times -5 \times -5\) is equivalent to \((-5)^4\), not \(-5^4\).

−1×−1×−1×−1×−1×−1−1×−1×−1×−1x−1×−1 is equivalent to (−1)6(−1)6 true or false

Let's break down the expression you've provided:

The expression \(-1 \times -1 \times -1 \times -1 \times -1 \times -1\) consists of six instances of \(-1\) multiplied together.

Since multiplying two negative numbers gives a positive result:

  • \((-1) \times (-1) = 1\)
  • \((-1) \times (-1) \times (-1) \times (-1) \times (-1) \times (-1) = 1 \times 1 \times (-1) = -1\)

Therefore, the entire product of six \(-1\) values is:

\[ (-1)^6 = 1 \]

Now, for the additional expression provided, which is \(-1 \times -1 \times -1 \times -1 \times -1 \times -1\):

  • The total expression simplifies to \((-1)^6\) as well.

Thus, we have two identical expressions:

\[ (-1 \times -1 \times -1 \times -1 \times -1 \times -1) = (-1)^6 \]

And also:

The statement suggests:

\[ (-1)^6(\text{-}1)^6 \text{ is equivalent to } (-1)^6 \times (-1)^6 \]

This statement is true because both sides evaluate to \(1 \times 1 = 1\).

So, the original statement is indeed true.